Education about various plastic types and its impact to environment for karang taruna group - Eko Hartini; Adian Khoironi; Dwi Puspa Oktaningtyas (Universitas Muhammadiyah Magelang, 2023)
The Karang Taruna Respect@05 group engages in waste bank management activities, but encounters challenges in sorting plastic waste. Additionally, the plastic product code provides information on the classification of plastic resin types, recommendations for usage, and guidelines for recycling plastic waste. This community service initiative aims to educate members of the youth organization about various types of plastic and their environmental impact, contributing to increased knowledge and enhanced plastic waste management efforts. The activities employ the outreach method, utilizing leaflets and interactive discussions. The results of this program indicate a notable increase in knowledge and support for sustainable plastic waste management.